2017
DOI: 10.1016/j.optlastec.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of silicon avalanche photodiode fabricated by CMOS process

Abstract: Avalanche photodiodes fabricated by CMOS process (CMOS-APDs) have features of high avalanche gain below 10 V, wide bandwidth over 5 GHz, and easy integration with electronic circuits. In CMOS-APDs, guard ring structure is introduced for high-speed operation by canceling photo-generated carriers in the substrate at the sacrifice of the responsivity. We describe here wavelength dependence of the responsivity and the bandwidth of the CMOS-APDs with opened and shorted guard ring structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In 2017, Napiah et al reported the development of a p-CMOS-type Si-APD using 0.18 µm CMOS technology. This device demonstrated a responsivity of 0.20 A/W at a bias voltage of 7.0 V and a wavelength of 405 nm [13]. In the same year, Xia et al utilized gradient boron doping technology to fabricate a highly sensitive silicon ultraviolet p+-i-n avalanche photodiode.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Napiah et al reported the development of a p-CMOS-type Si-APD using 0.18 µm CMOS technology. This device demonstrated a responsivity of 0.20 A/W at a bias voltage of 7.0 V and a wavelength of 405 nm [13]. In the same year, Xia et al utilized gradient boron doping technology to fabricate a highly sensitive silicon ultraviolet p+-i-n avalanche photodiode.…”
Section: Introductionmentioning
confidence: 99%
“…In [5]- [10], the Si photodiodes and photoreceivers were characterized only in 830 ∼ 850 nm wavelength region, and the maximum bandwidth of a few GHz and the maximum avalanche gain of more than 100 were achieved. We have also designed and realized avalanche photodiodes by standard CMOS process (CMOS-APD) and have characterized at 830 nm wavelength [11]- [14]. The avalanche gain of more than 100 was achieved at less than 10 V bias voltage, and the maximum bandwidth was 8.…”
Section: Introductionmentioning
confidence: 99%